Global economic prospects : (The World Bank, 2008)
Technology and technological progress are central to economic and social well being. The creation and diffusion of goods and services are critical drivers of economic growth, rising incomes, social and medical progress. Global Economic Prospects 2008: Technology Diffusion in the Developing World examines the state of technology in developing countries and the pace with which it has advanced since the early 1990s. It reveals both encouraging and cautionary trends. On the one hand, the pace of technological progress in developing countries has been much faster than in high-income countries reflecting increased exposure to foreign technology because of linkages with high-skilled Diasporas and the opening of these countries to international trade and foreign direct investment. On the other hand, the technology gap remains large, and the domestic factors that determine how quickly technologies spread within developing countries often stymie progress, especially among low-income countries. Repeating the rapid progress of this past decade will be difficult and may require that basic technology literacy is improved further; that government efforts to adapt and disseminate pre-existing technologies throughout the economy are strengthened; and that regulatory regimes are modified to encourage business innovation. This year s Global Economic Prospects comes on the heels of an extended period of strong growth and a 15-year period of strong performance in much of the developing world, which has contributed to substantial declines in global poverty. While high oil prices and heightened market volatility may signal a coming pause in this process, over the longer term continued technological progress should continue to push back poverty. The Global Economic Prospects provides essential information for those concerned with developments shaping today's global economy.